1991
DOI: 10.1073/pnas.88.10.4260
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and properties of a nitrile hydratase from the soil fungus Myrothecium verrucaria that is highly specific for the fertilizer cyanamide and cloning of its gene.

Abstract: A protein was purified from crude extracts of the soil fungus Myrothecium verrucaria by gel filtration and hydrophobic chromatography to homogeneity; this protein catalyzed the stoichiometric hydration of the fertilizer cyanamide to urea with high substrate specificity. This cyanamide hydratase (urea hydro-lyase; EC 4.2.1.69) contained zinc and consisted of six identical subunits with Mr = 27,700. It was partially sequenced. The protein was detectable only when the fungus was grown on cyanamide as the sole nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…Based on their protein sequence alignment and analysis, we developed a novel enzymatic assay and confirmed that the DDI2/3 genes encode a protein with CAH activity. Cyanamide hydratase enzymes have not been characterized to the level of many other enzymes, and to date there is only one report on CAH enzymatic activity based on proteins extracted from the fungus M. verrucaria (12). This study reports for the first time real time monitoring of a recombinant cyanamide hydratase reaction, and our recorded K m value for Ddi2/3 (17 mM) is comparable with that of the reported native M. verrucaria CAH (27 mM).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Based on their protein sequence alignment and analysis, we developed a novel enzymatic assay and confirmed that the DDI2/3 genes encode a protein with CAH activity. Cyanamide hydratase enzymes have not been characterized to the level of many other enzymes, and to date there is only one report on CAH enzymatic activity based on proteins extracted from the fungus M. verrucaria (12). This study reports for the first time real time monitoring of a recombinant cyanamide hydratase reaction, and our recorded K m value for Ddi2/3 (17 mM) is comparable with that of the reported native M. verrucaria CAH (27 mM).…”
Section: Discussionsupporting
confidence: 68%
“…2C), all belonging to Ascomycota. Among them, only CAH has been demonstrated to have a cyanamide hydratase activity (12,31), and Ddi2/3 and CAH appear to be distantly related (Fig. 2, B and C).…”
Section: Induction Of Two Duplicated Yeast Genes By Mms Treatment-mentioning
confidence: 99%
See 2 more Smart Citations
“…Brevibacterium (Arnaud et al, 1977), Arthrobacter (Asano et al, 1982), Nocardia (Harper, 1985), Klebsiella (Stalker et al, 1988), Corynebacterium (Li et al, 1992) and Rhodococcus (Langdahl et al, 1996)] and fungi [e.g. Fusarium solani (Harper, 1977), Myrothecium verrucaria (Maier-Greiner et al, 1991) and Fusarium lateritium (Cluness et al, 1993)l.…”
Section: Introductionmentioning
confidence: 99%